Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/biology12060809
|View full text |Cite|
|
Sign up to set email alerts
|

Plant–Fungi Interactions: Where It Goes?

Abstract: Fungi live different lifestyles—including pathogenic and symbiotic—by interacting with living plants. Recently, there has been a substantial increase in the study of phytopathogenic fungi and their interactions with plants. Symbiotic relationships with plants appear to be lagging behind, although progressive. Phytopathogenic fungi cause diseases in plants and put pressure on survival. Plants fight back against such pathogens through complicated self-defense mechanisms. However, phytopathogenic fungi develop vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 179 publications
0
7
0
Order By: Relevance
“…56 Importantly, they also interact under changing environmental conditions which makes the understanding of these interactions indispensable for future sustainable food production. 56 For example, it has been shown that ingestion of a symbiont does not preclude the evolution of beneficial interactions beyond simply host nutrition. 57 It was also hypothesized that fungi may interact as necessary symbionts with members of other human microbiome communities.…”
Section: Food Production For a Sustainable Futurementioning
confidence: 99%
“…56 Importantly, they also interact under changing environmental conditions which makes the understanding of these interactions indispensable for future sustainable food production. 56 For example, it has been shown that ingestion of a symbiont does not preclude the evolution of beneficial interactions beyond simply host nutrition. 57 It was also hypothesized that fungi may interact as necessary symbionts with members of other human microbiome communities.…”
Section: Food Production For a Sustainable Futurementioning
confidence: 99%
“…Extreme temperatures cause stress in plants, making them more susceptible to infections. 48 Temperature fluctuations can also affect the fungus's growth rate and development, as well as the host plants'. High humidity can create an ideal microclimate for fungal growth.…”
Section: Environmental Factors Affecting Pestalotiopsis Diseasementioning
confidence: 99%
“…Environmental stressors, such as intense rainfall or flooding, have the potential to accelerate disease spread by creating favorable conditions for spore dispersal and germination. 48,49 In contrast, prolonged periods of drought have the potential to diminish the vitality of plants and render them more vulnerable to infections. 50,51 The vegetation index is an effective tool for assessing plant health in relation to Pestalotiopsis disease.…”
Section: Environmental Factors Affecting Pestalotiopsis Diseasementioning
confidence: 99%
“…[1] They exist in any tissue at any stage of plant growth [2][3] and causes diseases in the plant itself through interactions with the plant, leading to a significant reduction in yield and quality in agriculture. [4][5] The use of fungicides is a major method to control plant pathogens, [6] but long-term use has led to problems such as drug residues, resistance, and environmental pollution. [7][8] Therefore, there is an urgent need to find new fungicides with high efficiency, low toxicity and no residue.…”
Section: Introductionmentioning
confidence: 99%
“…Plant pathogenic fungi have a very important impact on agricultural production [1] . They exist in any tissue at any stage of plant growth [2–3] and causes diseases in the plant itself through interactions with the plant, leading to a significant reduction in yield and quality in agriculture [4–5] . The use of fungicides is a major method to control plant pathogens, [6] but long‐term use has led to problems such as drug residues, resistance, and environmental pollution [7–8] .…”
Section: Introductionmentioning
confidence: 99%